Predictive Value of Cerebrospinal Fluid Biomarkers for Tap Test Responsiveness in Patients With Suspected Idiopathic Normal Pressure Hydrocephalus - Hua, Rongrong; Liu, Chunyan; Liu, Xing; Zhu, Jinwu; Zhang, Jie; Wang, Lidong; Shi, Zhe; Li, Jian; Kong, Shuangyan; Yang, Chenhui; Liu, Nan; Liu, Lijuan; et al. (Frontiers in Aging Neuroscience, 2021)
Background: The value of cerebrospinal fluid (CSF) biomarkers for assessing idiopathic normal pressure hydrocephalus (iNPH) must be determined. This prospective study aimed to reveal the correlation between CSF biomarkers and clinical symptoms of iNPH and the predictive value of these biomarkers for tap test responsiveness. Methods: Thirty-nine patients with suspected iNPH were recruited, contributed qualified CSF, and underwent a tap test and unified pre- and post-test evaluations of the neurological function. Results: The analysis of biomarkers from the patients’ CSF showed decreased levels of tau and its phosphorylated form, especially in the tap test (+) group. The responsiveness of the tap test was also related to the number of combined symptoms (p < 0.01), and a correlation was found between the end pressure or pressure difference in CSF and tap test responsiveness (p < 0.05). The results of the binary logistic regression analysis showed that P (tap test responsiveness) = 1/1 + e∧ − (−5.505 + 55.314 * ratio of p/T-tau − 1.586 * numbers of combined symptoms). The combined indicators (−5.505 + 0.553 * percentage of p/T-tau − 1.586 * numbers of combined symptoms) resulted in the highest sensitivity and specificity of 94.12% and 72.73%, respectively. Conclusions: CSF biomarkers may be assessed to judge tap test responsiveness, which is beneficial for the feasibility of a clinical application.